A Cross Sectional Study to Understand the Factors Affecting Intake of Supplementary Nutrition Among Children Registered with ICDS Anganwadis - MohamedAnas M Patni; Abhay Kavishwar; Mohmmedirfan H Momin; S L Kantharia (Medsci Publications, 2013)
Introduction: Malnutrition a serious problem in India. ICDS anganwadis provide supplementary nutrition to its children beneficiaries. Aims and objectives: 1) To study various factors affecting the intake of supplementary nutrition by children registered with anganwadis.2) To understand the mother's perception about supplementary nutrition provided at anganwadi centers. Methods: It was a cross sectional study done during January and February 2011. All children of three to five years of 6 randomly selected anganwadis of Jhagadia block of Bharuch district were selected for study. The pretested and predesigned questionnaire was used for collection of data from the mother of the children at their home. Data for availing of supplementary nutrition by child was obtained from anganwadis. Results: Out of 104 children, 70 (67.3%) received adequate and 34 (32.7) did not receive adequate supplementary nutrition. Among various factors, complementary feeding after 6 months of birth, birth weight, Vitamin A intake, diet at home, variety of food in diet at home and illness were found to have significant effect on attainment of supplementary nutrition by children from anganwadi. Also, mothers of children had good perception about supplementary nutrition in anganwadi, but considered it to be insignificant for growth of their child. Conclusion: Illness of child, diet at home, birth weight was few of the many factors found to have impact on intake of supplementary nutrition by child at anganwadi.